Differential expression of PEA3 in odontogenic cysts and tumors - Tun K.M. (2023)
Background: PEA3 transcription factor has been identified as a downstream target of the MAPK and PI3K pathways, and PEA3 overexpression has been observed in a variety of tumor types. We aimed to evaluate PEA3 expression in odontogenic cysts and tumors and compare the expression among odontogenic lesions. In addition, the correlations between PEA3 expression and clinicopathological characteristics of conventional ameloblastoma and unicystic ameloblastoma were investigated. Methods: This study was performed on 165 samples of odontogenic cysts and tumors including 20 dentigerous cysts, 20 odontogenic keratocysts, 16 adenomatoid odontogenic tumors, 5 ameloblastic fibromas, 45 unicystic ameloblastomas, and 59 conventional ameloblastomas. The sections were immunohistochemically stained with mouse monoclonal anti-PEA3 antibody and PEA3 expression was evaluated as the immunoreactive score. Results: PEA3 expression was absent in all dentigerous cysts (DCs) and odontogenic keratocysts, while all adenomatoid odontogenic tumors showed either no (75%) or low (25%) expression of PEA3. Most of the ameloblastic fibromas (60%) displayed no PEA3 expression. A high expression of PEA3 was observed in a substantial number of unicystic ameloblastomas (48.9%) and conventional ameloblastomas (49.2%) in our study. PEA3 expression in DCs, odontogenic keratocysts and adenomatoid odontogenic tumors were significantly different from that in conventional ameloblastomas and that in unicystic ameloblastomas (p < 0.05). The expression of PEA3 was significantly different in the age groups of unicystic ameloblastomas and histological subtypes of conventional ameloblastomas (p < 0.05). Conclusion: PEA3 overexpression is predominant in unicystic ameloblastomas and conventional ameloblastomas compared to other odontogenic lesions, indicating a pivotal role of PEA3 as a downstream effector of MAPK pathway in these two odontogenic lesions.